Deprivatization in the Philippines: Tipping the Public-Private Balance in Higher Education - Saguin, Kidjie (International Higher Education, 2025)
<h3 id="the-philippines-which-has-one-of-the-most-privatized-higher-education-systems-in-the-world-is-undergoing-a-puzzling-process-of-deprivatization-due-to-a-confluence-of-policies-that-have-turned-public-universities-and-colleges-into-demand-absorbing-institutions-despite-its-decreasing-share-in-overall-enrollment-private-higher-education-continues-to-experience-institutional-growth-led-by-an-increase-in-small-for-profit-private-higher-education-this-trend-presents-challenges-to-ensuring-public-private-complementarity" data-pm-slice="1 1 []">The Philippines, which has one of the most privatized higher education systems in the world, is undergoing a puzzling process of deprivatization due to a confluence of policies that have turned public universities and colleges into demand-absorbing institutions. Despite its decreasing share in overall enrollment, private higher education continues to experience institutional growth, led by an increase in small, for-profit private higher education. This trend presents challenges to ensuring public-private complementarity.